2007
DOI: 10.1007/s00134-007-0629-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between alveolar recruitment /derecruitment and inflection points on the pressure-volume curve

Abstract: In this physiological experiment in lungs with pure surfactant deactivation we found that individual alveolar recruitment measured by direct visualization was not correlated with the lower inflection point on inflation whereas alveolar derecruitment was correlated with alveolar derecruitment on deflation. These data suggest that inflection points on the P-V curve do not always represent a change in alveolar number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 14 publications
3
31
1
1
Order By: Relevance
“…Moreover, heterogeneous alveolar properties implicate heterogeneous opening pressures. These data provide an explanation for previous experimental observations that inflection points on the pv curve do not necessarily represent alveolar recruitment-derecruitment phenomena (DiRocco et al, 2007), which in fact occur successively over a wide range of lung volumes. Lung injury and disease typically affect not only one, but several characteristics of alveoli.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, heterogeneous alveolar properties implicate heterogeneous opening pressures. These data provide an explanation for previous experimental observations that inflection points on the pv curve do not necessarily represent alveolar recruitment-derecruitment phenomena (DiRocco et al, 2007), which in fact occur successively over a wide range of lung volumes. Lung injury and disease typically affect not only one, but several characteristics of alveoli.…”
Section: Discussionmentioning
confidence: 54%
“…Using the latter method, the relation of lung injury and corresponding changes in alveolar mechanics (10,(12)(13)(14)(15)(16), the effects of ventilator-induced lung injury on alveolar mechanics (17)(18)(19), the influences of PEEP (20)(21)(22)(23) and tidal volume (V^) (21,24), the relation of alveolar mechanics, recruitment-maneuvers and PEEP (22), and alveolar mechanics under quasi-static conditions (25,26) have been investigated.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…However, recent studies demonstrated that alveolar recruitment is a continuum phenomenon that occurs along the entire inflation limb of the P-V curve. A superior correlation was found between alveolar de-recruitment and the deflation limb of the P-V curve [5,6]. This finding may be explained by ventilation heterogeneity that has been observed in both healthy and injured lungs [7,8].…”
Section: Lung Recruitmentmentioning
confidence: 93%